(untitled) - Pinter, Harold (New York, 1967)
This play was first produced in London in 1965, and in New York City in 1967. In it, Teddy, a professor of philosophy who lives in America, brings his wife Ruth to England to visit his family, whom she has never met. His father, a widower, and two brothers, a pimp and a boxer, convince Ruth to remain with them and to enter a life of prostitution. Teddy returns to America alone. Pinter's very high talent manages to make the situation believable.
Keywords: Kịch tiếng Anh,English drama